Monitoring and control of vibrations due to blasting in Sumapaz tunnel, granting Bogotá-Girardot - Pinto-Morales, Luis Humberto; Fuentes-Fuentes, María del Carmen; Hernandez, Julián Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
This article discusses the most relevant topics of the subject of vibration of the ground, from its generation and monitoring to the control of their effects. We emphasize on the use and interpretation of the dynamic data field, since the theoretical methods and testing laboratory at times are not sufficient to solve applied geotechnical problems; for example, in the case of the assessment of the impact of the blasting in the Sumapaz tunnel, Boquerón area, department of Cundinamarca, Colombia. The work is the result of studies carried out by company I.GEOSOTMINE LTDA., in coordination with the Research Group INGEOFISICA of Universidad Pedagógica y Tecnológica de Colombia, on the exploration of the subsoil, aimed at the monitoring and control of blasting caused by explosive and micro-trepidation, in several Colombian regions.